PEMBENAHAN ETIKA PELAYANAN PUBLIK SEBAGAI IKHTIAR PENINGKATAN KUALITAS PELAYANAN PUBLIK - Winengan Winengan (Universitas Islam Negeri (UIN) Mataram, 2016)
The improvement of public services is one of homework for Indonesia that has not finished yet. Since the movement of reformation succeeds to remove the new regime, many policies have been produced by the government of reform era in increasing public services. However, such policies do not create satisfactory and enjoying public services. In many cases, citizens and their interest could not be the main concern. Even put aside from public service orientation. Ethic for public service is one of aspects of public services that is far from what the society expect. The attitude of public service officers who are not responsive, accommodative, ransparent, emphatic and friendly is ethic phenomena of public services. Such phenomena still can be seen from the way territory guardian when they interact with society in a given service process. But actually, the ethic of public services is an indicator of public service quality, especially in terms of services.